Audit of Population Administration Information System Risk (Case Study: City of Cimahi Population Service) - Muhammad Istambul; Iqbal Wijaya (Association for Scientific Computing Electrical and Engineering, 2020)
Cimahi City Population Service is one of the government agencies implementing population administration and is part of the public service. By implementing a good information system at the City of Population Office of Cimahi, it will improve the quality of services at the agency. The Population Administration Information System (SIAK) that has been implemented at the City Population Service in Cimahi has problems when the database cannot be accessed, the SIAK application cannot be run properly. Use that exceeds memory capacity can also cause SIAK errors such as too many electronic certificate requests that can overload the server, and SIAK cannot run due to errors in the attached network cable. It will cause risks that can disrupt public administration services so it needs to be measured and evaluated to find out whether the information technology implemented is appropriate and able to facilitate business processes. For this reason, it is necessary to conduct an information technology audit. The DSS domain used in this information system audit such as DSS01 Managing Operations. The audit framework used is COBIT 5 DSS domain (Deliver, Service, and Support) which is suitable for evaluating the risks that exist in SIAK. The DSS domain is considered to be following the existing information technology conditions in the current Population Office of Cimahi City. With the current state of information technology in the Population Service and the need to deliver services, serve and support information technology services.